1997
DOI: 10.1097/00004691-199701000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the Central and Peripheral Nervous System for the Control of Pain

Abstract: After suffering some setbacks since its introduction in 1967, stimulation of the spinal and peripheral nervous systems has undergone rapid development in the last ten years. Based on principles enunciated in the Gate Control Hypothesis that was published in 1968, stimulation-produced analgesia [SPA] has been subjected to intensive laboratory and clinical investigation. Historically, most new clinical ideas in medicine have tended to follow a three-tiered course. Initial enthusiasm gives way to a reappraisal of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 93 publications
1
63
0
2
Order By: Relevance
“…4,48 This opinion was con®rmed by a study of Barolat 35 who found that only patients with at least 50% pain relief at the time of implant were able to maintain the results over time. Di erent from most series on pain relief, however, Barolat did not use trial stimulation prior to the permanent implant.…”
Section: Ischemic Painmentioning
confidence: 98%
See 1 more Smart Citation
“…4,48 This opinion was con®rmed by a study of Barolat 35 who found that only patients with at least 50% pain relief at the time of implant were able to maintain the results over time. Di erent from most series on pain relief, however, Barolat did not use trial stimulation prior to the permanent implant.…”
Section: Ischemic Painmentioning
confidence: 98%
“…26 Patients with only intermittent claudication or severely disabled patients who have also tissue loss like gangrene and ulcers respond less successfully to SCS treatment. 48 Patients with stage IV disease may respond to SCS, since ischemic ulcers 53 cm in diameter have been shown to heal well in response to stimulation. 49,50 In patients with established gangrene, no e ect from SCS will be obtained.…”
Section: Ischemic Painmentioning
confidence: 99%
“…SCS has been used to treat lower limb pain syndrome 5,8,15) . Severe CRPS start frequently at a focal point but then spreads to involve other limbs, and can become an almost systemic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with chronic peripheral nerve injury showed the best response 1,13,16) . Patients suitable for this form of neuromodulation include those with peripheral mononeuropathy (traumatic, idiopathic, or iatrogenic), a chronic entrapment syndrome, and CRPS 3,4,11,15) . The best predictor for success using a PNS implant to treat intractable pain is accurate patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…55,56 In conclusion, neuromodulation studies show some efficacy in the acute and preventive treatment of migraine. The results of vagal nerve stimulation are promising and sphenopalatine ganglion stimulation studies might be very interesting and may shed light into our understanding of pathomechanism of headache.…”
Section: 54mentioning
confidence: 90%